Effects of in vitro exposure to butylparaben and di-(2 ethylhexyl) phthalate, alone or in combination, on ovarian function - Guerra, Marina T. [UNESP]; Furlong, Hayley C.; Kempinas, Wilma G. [UNESP]; Foster, Warren G. (Wiley, 2016)
Parabens and phthalates are commercial chemicals widely used in the manufacture of industrial and consumer products frequently found as contaminants in biological fluids. We evaluated the effects of di-(2-ethylhexyl) phthalate (DEHP) (ranging from 10–9 to 10–7 m [1–100 nm; 0.39–39 ng ml–1]) and butylparaben (BP) (ranging from 10–8 to 10–5 m [10 nm–10 μm; 1.9 ng ml–1 to 1.9 μg ml–1]), alone and in combination, on isolated mouse preantral follicle and human granulosa cell (hGC) cultures to study direct effects on follicle growth and ovarian steroidogenesis. Our results revealed that, in follicle culture, DEHP and BP attenuate estradiol output but only when present together. DEHP decreases progesterone concentrations in the spent media of hGC cultures, an effect that was attenuated when BP was added together with DEHP. Although changes in steroidogenesis were observed, no effects on follicular development or survival were noted in the culture systems. We suggest that BP and DEHP act with additive effect to decrease estradiol production whereas at later stages of follicle development BP blocks the effect of DEHP in hGCs resulting in decreased progesterone output. Taken together our results suggest that DEHP and BP adversely affect steroidogenesis from the preantral stage onward and the effects of these chemicals are both stage-dependent and modified by co-exposure. Copyright © 2016 John Wiley & Sons, Ltd.
Keywords: follicle culture; granulosa cell; Paraben; phthalate; steroidogenesis